The Relationship Between Self Efficacy and Academic Flow in Junior High School Students: Hubungan Antara Self Efficacy dengan Flow Akademik pada Siswa Sekolah Menengah Pertama - Rochmawati, Rochmawati; Nastiti, Dwi (Indonesian Journal of Education Methods Development, 2022)
This research is motivated by a phenomenon where there are students of SMP Muhammadiyah 8 Tanggulangin Sidoarjo who have not experienced academic flow conditions such as not being able to concentrate fully, not fully paying attention to the delivery of material when the teacher explains, or doing other activities during the learning process. This study aims to determine the relationship between self-efficacy and academic flow in students of SMP Muhammadiyah 8 Tanggulangin Sidoarjo. This research is a type of correlational quantitative research. The population in this study were students of SMP Muhammadiyah 8 Tanggulangin Sidoarjo, totaling 174 students. The sampling technique used is saturated sampling so that the number of samples is 174 students. The data collection in this study used the self-efficacy scale and the academic flow scale. The reliability on the academic flow scale is 0.874 and the reliability on the self-efficacy scale is 0.826. The data analysis technique uses Pearson's Product-Moment correlation with the help of SPSS 16.0 for windows. The results of the research data analysis showed a correlation coefficient (rxy) of 0.465 with a significance of 0.000 <0.05, which means that there is a significant positive relationship between self-efficacy and academic flow at SMP Muhammadiyah 8 Tanggulangin Sidoarjo.